Skrining Awal dan Edukasi Pencegahan Gangguan Fungsi Hati Berbasis Komunitas di Yayasan Baptis Cengkareng - Singh, Arwinder; Gunaidi, Farell Christian; Santoso, Alexander Halim; Goh, Daniel; Gracienne Gracienne (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Liver disease is a health problem that often goes undetected in its early stages due to the absence of specific symptoms, despite the liver's vital role in metabolism, detoxification, and maintaining homeostasis. Early detection is crucial to prevent the progression of liver dysfunction. This community service activity aimed to raise public awareness of the importance of early liver disease screening through the examination of lipid ratios (total cholesterol/HDL and triglycerides/HDL) and physical evaluation for clinical signs of liver dysfunction. The program was conducted at the Cengkareng Baptist Foundation and involved 59 adult participants. The screening included basic laboratory tests and direct physical examinations, followed by health education tailored to each participant based on their screening results. Findings revealed that 83.1% of participants had elevated triglyceride/HDL ratios and 28.8% had total cholesterol/HDL ratios above the normal range, although 100% showed no physical signs suggestive of liver disease. These results indicate the presence of underlying metabolic risks that may affect liver function. This program had a positive impact by enhancing public understanding of the importance of a healthy lifestyle and regular check-ups as part of health promotion and disease prevention efforts related to liver health. Keywords: Early Detection, Liver Function, Lipid Ratio, Health Education, Community Service